2019
DOI: 10.1016/j.jclepro.2019.117950
|View full text |Cite
|
Sign up to set email alerts
|

Engineering properties of crumb rubber alkali-activated mortar reinforced with recycled steel fibres

Abstract: To mitigate the potential problems of waste tyres and Portland cement greenhouse gas emissions while further promote the sustainable development of construction industry, this paper, for the first time, explores the workability and mechanical properties of crumb rubber alkali-activated fly ash-slag mortar reinforced with recycled tyre steel fibre (RSFRAM) considering different contents of crumb rubber (CR, i.e. 5%, 10% and 15% replacement by volume of fine aggregate) and recycled tyre steel fibre (RTSF, i.e. 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 64 publications
4
33
0
1
Order By: Relevance
“…RTSF (see Fig. 1a and b) (Zhong et al, 2019) and PPF (see Fig. 1c and d) were used as reinforcing fibres in this study.…”
Section: Experimental Programmementioning
confidence: 99%
See 2 more Smart Citations
“…RTSF (see Fig. 1a and b) (Zhong et al, 2019) and PPF (see Fig. 1c and d) were used as reinforcing fibres in this study.…”
Section: Experimental Programmementioning
confidence: 99%
“…Four-point bending tests on three prismatic samples (100 Â 100 Â 500 mm) at 28 d were conducted as per ASTM C1018 (1997) to determine the flexural behaviour of all mixtures, where the previous work (Zhong et al, 2019) found that this standard was more suitable for describing the flexural behaviour of FRC with deflection-hardening feature. A controlled displacement rate of 1 mm/min was adopted for all flexural testing in this study.…”
Section: Flexural Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the increasing energy consumption (about 15% of the total building energy) and generated environmental pollution by manufacturing the aforementioned fibres [30][31][32] motivated researchers to explore the possibility of utilizing end-of-life materials (e.g. waste tyres) as fibre reinforcement constituents.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement may be due to the hydrophilic nature of SF [36], improving the bond between SF and matrix. Also, high elastic modulus of SF facilitates stress distribution so that tensile crack formation is restrained, improving the mechanical strengths [37].…”
Section: Flexural Strengthmentioning
confidence: 99%